1989
DOI: 10.1159/000261217
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Glucose in Oral Fluid at Different Sites in the Mouth

Abstract: Using glucose as a marker, a detailed study of retention at 5 different sites in the mouth of 1 subject and a less detailed examination of 4 selected sites in the mouths of 10 other subjects revealed site-specific differential patterns of oral retention (or clearance). These patterns seemed independent of sometimes large, absolute day-to-day variations in oral retention which occur in all subjects but appeared to vary somewhat between subjects, probably reflecting slight differences in the anatomy and physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…The clearance halftimes on the buccal surfaces of the upper anterior teeth were the longest of any site in the mouth. Weatherell, et al [2] and Watanabe [3] reported the same results. These show that the saliva secreted into oral cavity is not perfectly mixed.…”
Section: Introductionsupporting
confidence: 57%
“…The clearance halftimes on the buccal surfaces of the upper anterior teeth were the longest of any site in the mouth. Weatherell, et al [2] and Watanabe [3] reported the same results. These show that the saliva secreted into oral cavity is not perfectly mixed.…”
Section: Introductionsupporting
confidence: 57%
“…A low pH at the site below the contact area could lead to an increase in the proportions of lactobacilli and streptococci in plaque at this site. In addition to saliva exclusion, carbohydrate tends to be retained in stagnant sites, especially below the contact area [Kleinberg, 1977;Weatherell et al, 1989], a situation possibly enhanced by increased sugar intake [Wilson and Ashley, 1990] by approximal plaque. It was not practicable to ascertain meaningful data concerning fluoride supplement or sugar consumption from the study group, so the longitudinal history of the relatively low proportion of lesions was not available.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 It has been suggested that the anatomy and physiology of the mouth, including interproximal spaces, occlusion and soft tissue anatomy may influence the retention or clearance or liquids in the mouth. [32][33][34] The multifactorial analysis completed by Al-Malik et al 28 also found a significant association between erosion and frequency of fizzy drink consumption, with an odds ratio of 1.46, but this was for 2-5-year-olds. The demonstration of increased risk is not the same as the identification of aetiology and attempts to show a causal relationship between risk factors and erosion have failed, although the sample sizes were small.…”
Section: Main Studymentioning
confidence: 99%